Indicators for prediction of Mycobacterium tuberculosis positivity detected with bronchoalveolar lavage fluid - Xi Liu; Xing-Fang Hou; Lei Gao; Guo-Fang Deng; Ming-Xia Zhang; Qun-Yi Deng; Tao-Sheng Ye; Qian-Ting Yang; Bo-Ping Zhou; Zhi-Hua Wen; Hai-Ying Liu; Hardy Kornfeld; et al. (BMC, 2018)
Abstract Background The diagnosis of active pulmonary tuberculosis (TB) remains a challenge in clinic, especially for sputum negative pulmonary TB. Bronchoalveolar lavage fluid (BALF) has higher sensitivity than sputum for detection of Mycobacterium tuberculosis (Mtb). However, bronchoscopy is invasive and costly, and not suitable for all patients. In order to make TB patients get more benefit from BALF for diagnosis, we explore which indicator might be used to optimize the choice of bronchoscopy. Methods A total of 1539 sputum-smear-negative pulmonary TB suspects who underwent bronchoscopy were recruited for evaluation. The sensitivity, specificity and accuracy of Mtb detection in sputum and BALF were compared. Odds ratios and 95% confidence intervals were used to assess variables that associated with positive acid-fast bacilli (AFB) smear, Mtb culture and nucleic acid amplification test (NAAT) of BALF in sputum-negative and non-sputum-producing pulmonary TB suspects. Results BALF has significantly higher sensitivity (63.4%) than sputum (43.5%) for Mtb detection by culture and NAAT. 19.7% (122/620) sputum-negative and 40.0% (163/408) non-sputum-producing suspects had positive bacteriological results in BALF. Among sputum-negative and non-sputum-producing pulmonary TB suspects, the positivity of Mtb detection in BALF is associated with a younger age, the presence of pulmonary cavities and a positive result of interferon-gamma release assay (IGRA). Sputum-negative patients under 35 years old with positive IGRA and pulmonary cavity had 84.8% positivity of Mtb in BALF. Conclusions Our study indicated that combination of age, the presence of pulmonary cavity, and the result of IGRA is useful to predict the positivity of Mtb detection in BALF among sputum-negative and non-sputum producing pulmonary TB suspects. Those who are under 35 years old, positive for the presence of pulmonary cavity and IGRA, should undergo bronchoscopy to collect BAFL for Mtb tests, as they have the highest possibility to get bacteriologically confirmation of TB.